Subclinical Leaflets Thrombosis After Transcatheter Replacement of Bicuspid vs. Tricuspid Aortic Valve - Zhu, Gangjie; Fan, Jiaqi; Zhou, Dao; Dai, Hanyi; Zhu, Qifeng; He, Yuxin; Guo, Yuchao; Wang, Lihan; Liu, Xianbao; Wang, Jian'an (Frontiers in Cardiovascular Medicine, 2021)
Background: Subclinical leaflet thrombosis (SLT) is an important sequela that compromises the durability of the bioprosthetic valve. Objectives: To better determine the effect of SLT in bicuspid aortic valve (BAV), we performed a retrospective assessment of CT-defined SLT in BAV and tricuspid aortic valve (TAV) stenotic patients. Methods: We consecutively collected patients undergoing the TAVR between August 2015 and March 2020 in our center. A total of 170 BAV and 201 TAV cases were enrolled. Multidetector computed tomography was performed within 30 days and at 1-year. Results: Twenty cases in the BAV group and 19 cases in the TAV group had hypoattenuated leaflet thickening (HALT) in 30 days (12.5% vs. 9.9%, p=0.449), and 52 cases in BAV and 61 cases in TAV had the HALT (34.9% vs. 36.7%, p= 0.733) at 1-year follow-up. The mean aortic gradient (MAG) and effective orifice areas (EOA) values were comparable between the two groups at 30 days (HALT vs. no HALT; 10.8±4.8 vs. 11.3±6.0, p=0.638; 1.6±0.4 vs. 1.6±0.3, p=0.724), and still, no difference was observed in the MAG at 1-year (11.5±5.6 vs. 10.6±5.1, p=0.164). However, the EOA at 1-year was statistically different between the two groups (1.5±0.3 vs. 1.6±0.4, p=0.004). The multivariate logistic regression analysis demonstrated the anticoagulation and age as independent predictors both in the BAV and TAV groups at 1-year. There was no difference in clinical events between the HALT and no HALT group in relevant to BAV or TAV. Conclusions: The presence of subclinical leaflet thrombosis defined by the CT was comparable between the BAV and TAV in the first year after the TAVR procedure. Age and anticoagulation were the independent predictors of the subclinical leaflet thrombosis at 1 year after the TAVR. There was no difference in relevant clinical events between the BAV and TAV groups.